Chapter Territorial transformations, landscape and architectural features of the "Tenuta di Isola Sacra" in the reclamation of the early 1900s - Alati, Maria Chiara (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The paper presents the first acquisitions relating to the transformations of Isola Sacra, in the Agro Romano, between the end of the 19th century and the first half of the 20th century, implemented through the land reclamation and enhancement work started by Genio Civile and completed by the Opera Nazionale Combattenti. The intent is to return a crucial phase of the territorial development of the area to recompose the overall image of a context that suffered uncontrolled transformations and in which it is difficult, today, to identify the architectural and landscape features left by this significant and recent past.